Persistence of social media on political activism and engagement among Indonesian and Pakistani youths. (30th October 2020) - Ida, Rachmah; Saud, Muhammad; Mashud, Musta'in
In recent years, the emergence of social media has encouraged and influenced our youth to participate in political matters. The current study was conducted in Indonesia and Pakistan. The objective of the study was to analyse the persistence of social media and youth political participation in democratic activities. The study opted quantitative research design through an offline and online survey to obtain data from 400 individuals (falling in age group 18th to 29th), having political experience and knowledge of participation. The data gathered through structured questionnaires using scales to compile the results, and data was carried out through Excel and SPSS software. The results show that social media is a persuasive medium in providing platform to youth to participate in political activism. Youth healthy engagement in such activities plays a significant role in the political structure of states. It was also observed that youth participation is essential for prosperity and growth of nation. The study suggests that the Government of Indonesia and Pakistan have a good opportunity to socialise youths through online spheres.